Stres Kerja, Kompensasi dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan PT Autostar - Steven, Steven; Akbar Batubara, Faisal; Putra, Ricky; Fahmi, Muhammad (Journal of Management and Bussines (JOMB), 2024)
The purpose of this study was to test and analyze the effect of work stress, compensation and work environment on employee job satisfaction at PT Autostar Mandiri Teknotama Medan. This study is a descriptive study. The population and sample of this study were 67 employees of PT. Autostar Mandiri Teknotama with a saturated sampling technique. The statistical method used was multiple linear regression analysis. The results of the study showed that partially stated work stress, compensation and work environment had a significant effect on employee job satisfaction at PT Autostar Mandiri Teknotama Medan. And also simultaneously stated that all independent variables had a significant effect on employee job satisfaction at PT Autostar Mandiri Teknotama Medan. Conclusion, simultaneously and partially work stress, compensation and work environment had a significant effect on employee job satisfaction at PT Autostar Mandiri Teknotama Medan. Keywords: Compensation, Employee Job Satisfaction, Work Environment, Job Stress